Cadmium armors the Cd hyperaccumulator Sedum alfredii against aphid attack - Xu, Lingling; Lu, Lingli; Lin, Xianyong; Hu, Yan (Frontiers in Environmental Science, 2022)
The cadmium (Cd) hyperaccumulator Sedum alfredii has been identified to have great ability in accumulating > 100 ppm (dry weight) of Cd in its aboveground, but virtually little attention had been paid to the possibility that S. alfredii might benefit from this trait. Here we investigated the effect of Cd accumulation on performance of the black bean aphid Aphis fabae in this plant species. The results showed that six weeks Cd exposure prevented the plants of S. alfredii from being infested by aphids. Another separate experiment, S. alfredii pretreated with 100 μM CdCl2 for 7 days, and prolonged Cd exposure for another 7 days with aphid condition, showed that significantly reduced the number of aphids in the Cd-pretreated S. alfredii at the end of 7 d with aphid condition, and the concentration of Cd in the phloem exudates of S. alfredii also had high level. Meantime, the micro XRF mapping of aphids collected from Cd-treated plants contained high Cd levels in the stylets. In summary, Cd protects S. alfredii from A. fabae due to toxicity but not deterrence, which may be related to the abundant Cd in phloem.